2020
DOI: 10.1175/jamc-d-19-0195.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of WRF urban schemes and PBL schemes over Dallas Fort Worth during a dry summer and a wet summer

Abstract: This study evaluated the Weather Research and Forecasting (WRF) model sensitivity to different planetary boundary layer (PBL) schemes (the YSU and MYJ schemes) and urban schemes including the bulk scheme (BULK), single-layer urban canopy model (UCM), multi-layer building environment parameterization (BEP) model, and multi-layer building energy model (BEM). Daily reinitialization simulations were conducted over Dallas-Fort Worth during a dry summer month (July 2011) and a wet summer month (July 2015) with weake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The UCM scheme uses Monin–Obukhov similarity theory and the Jurges formula to calculate sensible heat flux (Kusaka et al., 2001). While BEP considers the three‐dimensional structure of the urban region along with the shadow, reflection and trapping of the radiation leading to relatively higher sensible heat flux than UCM during the daytime (Huang et al., 2019; Wang et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The UCM scheme uses Monin–Obukhov similarity theory and the Jurges formula to calculate sensible heat flux (Kusaka et al., 2001). While BEP considers the three‐dimensional structure of the urban region along with the shadow, reflection and trapping of the radiation leading to relatively higher sensible heat flux than UCM during the daytime (Huang et al., 2019; Wang et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, two potential planetary boundary layer (PBL) schemes are compared in terms of performance and need of bias correction: the commonly used Bougeault–Lacarrère scheme (BouLac; Bougeault and Lacarrere 1989 ) for urban simulations that use BEP–BEM and the recently coupled YSU scheme to BEP–BEM ( Hong et al 2006 ; Hong and Kim 2008 ; Hendricks et al 2020 ). Although we found that the latter performed better over the two hottest days of summer 2018 (see appendix A ), we decided to keep a simulation with BouLac as YSU has only been applied over Dallas ( Wang and Hu 2021 ), whereas BouLac has been used in multiple studies already (e.g., Salamanca et al 2011 , 2012 ; Gutiérrez et al 2015 ; Tewari et al 2017 ; Mughal et al 2019 ). The Mellor–Yamada–Janjić (MYJ; Janjić 1994 , 2001 ) scheme, also available for BEP–BEM simulations, is disregarded in this study since this PBL scheme is especially used for mountainous terrain ( Zonato et al 2022 ), and we are modeling the relatively flat terrain of southeast England.…”
Section: Methodsmentioning
confidence: 99%
“…The cooler plain and mountains over South China at night could be partially attributed to uncertainties associated with the land surface model, the PBL and SL parameterizations, and the lack of an urban canopy model with more accurate representation of the UHI effects (e.g., Ferrero et al., 2018; M. Huang et al., 2018; Johnson et al., 2021; J.‐X. Wang & Hu, 2021). The cool bias of T 2m during the nocturnal hours over the key region (Table 2) indicates that the SHORT simulations could possibly overestimate the strength of land breeze, which could partially contribute to the weaker southerly wind component in the PBL on the coasts and could also lead to less potential energy on land for developing convection, together contributing to the underestimation of nocturnal rainfall over the key region.…”
Section: Evaluation Of Seasonal Nocturnal Rainfall and Associated Lar...mentioning
confidence: 99%
“…Huang et al, 2018;Johnson et al, 2021; J.-X. Wang & Hu, 2021). The cool bias of T 2m during the nocturnal hours over the key region (Table 2) indicates that the SHORT simulations could possibly overestimate the strength of land breeze, which could partially contribute to the weaker southerly wind component in the PBL on the coasts and could also lead to less potential energy on land for developing convection, together contributing to the underestimation of nocturnal rainfall over the key region.…”
Section: Comparison Between the Short And The Observationsmentioning
confidence: 99%